Research on the potential of photovoltaic technologies in reducing energy consumption in an urban mixed use residential community. A Case study for net zero energy community in Dubai, UAE. - SUGATHAN, SANAL (2018)
Humans have an unquenchable thirst for energy. Accelerated global economic and population growth are the main influencing factors that has led to the increase in electricity consumption. In addition, the release greenhouse gas (GHG) emissions from energy resources such as the fast depleting fossil fuels whose prices are rising globally. Therefore, the key challenge is to reduce the consumption of fossil fuels which decreases the production of greenhouse gases such as CO2 and CH4 by using renewable energy technologies to provide clean carbon free energy that can combat future energy security challenges. Even though UAE has huge amount of solar resources available which if harnessed could resolve the energy crisis, much of it goes to waste. This is mainly because most of its domestic energy needs are meet by subsidized electricity tariffs in Abu Dhabi also to blame for their high per capita GHG emissions. The outcome of these events, abundant regional solar irradiation and drop in global PV prices has led to the significant developments and innovations in the solar energy sector. Consequently, a trending holistic integrated approach where renewable technologies such as solar photovoltaic’ integrated on built environment at the community scale, namely the Net Zero Energy Community (NZEC) is paving way to future smart sustainable cities. NZEC are the next frontier in energy efficiency and play a key role in fulfilling Dubai’s ambitious sustainable targets by reducing the local carbon footprint with the help of a series of optimized and well balanced operations between energy consumption and production coupled with successful grid integration of photovoltaic energy technologies. Reaching net zero energy (NZE) status across every single building may not be feasible, but it is realistic if we evaluate them with their connected systems as a collective unit at the community scale. While, tangible benefits to the community such as internal exchange of energy, load diversity, reduction in dependency of electricity grid, reduction of long power transmission cables, substation sizes have been recognized. The dissertation adapts the IES-VE computer simulation methodology to support the several applications of photovoltaic technologies that assist in the compensation of overall energy consumption for an existing community in the UAE to achieve net zero energy status. This paper illustrates the many strategies to bridge the deficiency energy gap in three categories; 1) increase PV panel energy production by optimizing the orientation, inclination angle, manual tracking, enhanced microcontrollers and inverters, 2) increase PV panel efficiency from better manufacturers, 3) increase the area of PV panel installation on the building fabric and exploring options beyond the building footprint at the community level. The initial scenarios were simulated for the most optimum PV orientations, fixed inclination tilt angle, module technology, inverter and controller technology. The results reveal that the highest energy generation was the south facing polycrystalline PV panels at 25° fixed inclination tilt angle. With the enhancement of cost effective Maximum Power Point Tracking (MPPT) device and the addition of transformerless inverters increased the overall power output of polycrystalline from 216 KWh/m² to 262 KWh/m². Polycrystalline technologies with higher energy efficiencies from different manufacturers with 18.15% module efficiency were simulated resulting in 24% energy generation more than the base case panel with 16% module efficiency but from an economic point of view it is not a cost-effective solution due to its high cost per production AED/KWh rate. Additional benefits of integrating PV panels on rooftops were noticed though passive panel shading which minimized the solar gain and reduced the overall community energy consumption. On the account, insufficient rooftop area for PV installation that can compensate for the total community energy consumption, various scenarios for increasing the area of PV installation on the building envelope and options beyond the building footprint at the community level were explored. In this scenario, for aesthetic reasons the PV angles were changed to 2° inclination tilt angle. The Integration of community solar street lighting, additional PV panel installation on solar car parking integration, greenhouse PV farm, children’s play area, multipurpose events park and PV covered walkway resulted in a surplus PV area of 736.58 m² for energy generation. These results prove that it is possible and feasible to convert an existing urban mixed use community to a Net Zero Energy Community in Dubai with a reasonable overall payback period of 4 years. This research will provide as a stepping stone and support the Dubai government, policy makers, market stakeholders; private developers work together, develop objectives and achieve the set target towards Dubai Clean Energy Strategy 2050 for a net positive built environment and decarbonized global economy.